Technical Aspects of Waste Shelter Facility Layout Building Planning in Udayana University Sudirman Campus - Pradana, Mohammad Zakariya; Madrini, Ida Ayu Gede Bintang; Aviantara, I Gusti Ngurah Apriadi (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
One of the places that has the potential to generate waste is a universityorcampus. With routine activities, of course there are various types of waste that can be generated every day, namely, paper waste, plastic waste, wet waste, medical waste, residual waste, and glass waste. Not all of the existing waste collection building facilities in the University have a layout that is in accordance with the 3R (reduce, reuse, and recycle) waste processing site (TPS) concept. Judging from the waste generated, which is 4.91 m³/day, and the weight of the waste is 270.82 kg/day, Udayana University should have a garbage collection facility that is able to manage 214waste in an integrated manner. The purpose of this study was to find out the opinion of the community regarding the need for waste collection facilities on the Sudirman Campus and to determine the feasibility of planning the layout of the 3R TPS contained in the 2017 TPS 3R technical guidelines standard at the SudirmanCampus, Udayana University in terms of technical aspects. The primary data was obtained by using the observation method and using a questionnaire, while the secondary data was obtained from the study of literature related to the 3R TPS. The results of thestudy using the questionnaire method, obtained an average score of 85.5%, which means that respondents strongly agree with the procurement of waste collection facilities on the Sudirman Campus, and obtained an average score of 84.5%, which means strongly agree with the existence of building facilities. according to the technical standard criteria of the 3R TPS building, while in the technical aspect it produces a waste management plan in the form of storage, collection, transfer, transportation, and waste processing.planning is layout TPS 3Rplanned to have 10 areas. In the location planning, it is planned to be built in the Sudirman Campus area with an area of 184 m², with building construction planning in accordance with the TPS 3R 2017 Technical Guidelines Standard, as well as proper road accessibility and utilities or supporting facilities such as electrical installations, water installations, communal containers, barriers, sanitation rooms, and drainage channels.